2021
DOI: 10.3390/cells10092425
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression Network Analysis of MicroRNAs and Proteins in Severe Traumatic Brain Injury: A Systematic Review

Abstract: Traumatic brain injury (TBI) represents one of the leading causes of mortality and morbidity worldwide, placing an enormous socioeconomic burden on healthcare services and communities around the world. Survivors of TBI can experience complications ranging from temporary neurological and psychosocial problems to long-term, severe disability and neurodegenerative disease. The current lack of therapeutic agents able to mitigate the effects of secondary brain injury highlights the urgent need for novel target disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 102 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…TBI affects over 2.5 million people in the USA and Europe and leads to serious disability in around 40 % of involved patients [16]. Previous studies supported the role of various protein and gene dysregulation in brain sensitivity and recovery in TBI diseases [19,63,64]. Statins in numerous investigations displayed a role in ameliorating post-TBI implications.…”
Section: Discussionmentioning
confidence: 99%
“…TBI affects over 2.5 million people in the USA and Europe and leads to serious disability in around 40 % of involved patients [16]. Previous studies supported the role of various protein and gene dysregulation in brain sensitivity and recovery in TBI diseases [19,63,64]. Statins in numerous investigations displayed a role in ameliorating post-TBI implications.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous reports investigating the alterations of miRNAs following TBI, these studies were mostly performed in blood or CSF as potential biomarkers [ 26 , 37 ]. The studies carried out in brains of animal models of TBI have revealed different patterns, depending on the time post-injury, the brain region investigated, the model used, and the severity of the injury [ 23 , 38 , 39 , 40 , 41 ]. For instance, one of the first reports carrying out miRNA studies in animal models of TBI reported altered expression levels of miR-107, -130a, -223, -292-5p, -433-3p, -451, -541, and -711 immediately post-injury [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed 2 weeks post-injury are scarce [ 43 ] and do not involve the analysis of the pericontusional tissue. A recent meta-analysis of 34 studies performed in severe TBI models revealed that the most common pathways regulated after TBI by miRNAs involve the TNFα and endocytosis signalling [ 41 ]. Interestingly, the list of miRNAs involved included miR-107 and miR-181b, which were also found altered in our study.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs also play a crucial role in various physiological and pathological processes such as cell growth, differentiation, metabolism, apoptosis, angiogenesis, and tumorigenesis. miRNAs play an essential role in maintaining and regulating physiological functions in various diseases, including TBI, and therefore are receiving increasing attention in disease diagnosis and treatment targets [20] [21] [22] . miR-425-5p, miR-16, miR-92a, and miR-765 are abnormally expressed in patients with TBI and have high diagnostic values [23] .…”
Section: Introductionmentioning
confidence: 99%